La réception des notions philosophiques de trace, d’arkhé et de document dans l’œuvre d’Alain Nadaud - Chiadini, Gianluca (Labyrinth, 2020)
The reception of the notions of trace, arkhé, and document in the work of Alain Nadaud This paper intends to point out the philosophical features in the novels of the French writer Alain Nadaud and their links with the philosophical theory concerning the concepts of trace, arkhé and document elaborated by Jacques Derrida in the second half of the XX century. This subject, related to the contemporary socio-historical concept of post-truth, reveals the originality and the up-to-date tendency in the novels of Alain Nadaud. This paper uncovers new important aspects of his work by proposing a solid philosophical interpretation of its main theoretical principles. In particular, it uncovers the philosophical reasons at the origin of his writing, which is based on the historical research method. Furthermore, it reveals the sense of dystopia of his novels and relates it with the most recent socio-philosophical analysis of contemporary western society.